1997
DOI: 10.1074/jbc.272.44.27893
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Trichohyalin

Abstract: Trichohyalin (THH) is a major structural protein of the inner root sheath cells and medulla layer of the hair follicle and, to a lesser extent, of other specialized epithelia. THH is a high molecular weight insoluble ␣-helixrich protein that forms rigid structures as a result of postsynthetic modifications by two Ca 2؉ -dependent enzymes, transglutaminases (TGases) (protein cross-linking) and peptidyl-arginine deiminase (conversion of arginines to citrullines with loss of organized structure). The modified THH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 49 publications
5
69
0
2
Order By: Relevance
“…Previous investigation has shown that this irreversible modification unfolds the protein structure of natural substrates, such as filaggrin in the skin epidermis and trichohyalin in the hair follicle (13), resulting in different outcomes. Citrullinated filaggrin disassociates from keratin filaments and is hydrolyzed into amino acids (13), whereas citrullinated trichohyalin becomes soluble and susceptible to cross-linking by another Ca 2ϩ -dependent enzyme, transglutaminase (16,17). In contrast, citrullinated S100A3 dimer assembled into a homotetramer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigation has shown that this irreversible modification unfolds the protein structure of natural substrates, such as filaggrin in the skin epidermis and trichohyalin in the hair follicle (13), resulting in different outcomes. Citrullinated filaggrin disassociates from keratin filaments and is hydrolyzed into amino acids (13), whereas citrullinated trichohyalin becomes soluble and susceptible to cross-linking by another Ca 2ϩ -dependent enzyme, transglutaminase (16,17). In contrast, citrullinated S100A3 dimer assembled into a homotetramer.…”
Section: Discussionmentioning
confidence: 99%
“…Although this biochemical process is believed to be precisely regulated by the intracellular Ca 2ϩ concentration, there remains controversy regarding the mechanism by which PAD and transglutaminase could be activated in vivo, since both require a nearly millimolar level of Ca 2ϩ to exhibit their full activities in vitro (12,18). Several epithelial protein barrier components containing Ca 2ϩ -binding domains have been reported to be natural substrates of PAD (the mature filaggrin subunit, proteolytically processed from profilaggrin (13)) or of transgutaminase (S100A7, S100A10, and S100A11 (14,15)) in skin epidermis or of both these enzymes (trichohyalin (16,17)) in hair follicles. It has been proposed that the Ca 2ϩ ions bound to these proteins are presented to the Ca 2ϩ -dependent proteinmodifying enzymes (8,11); however, more direct evidence is necessary to support this notion.…”
mentioning
confidence: 99%
“…The recently discovered TGase 5 (originally named X) enzyme awaits characterization (8). TGase 1 is essential for the cross-linking of substrates such as loricrin (9), trichohyalin (10), and SPRs 1 (11), 2 (12), and 3 (13). However, as observed in lamellar ichthyosis, a genetic defect of TGase 1, TGases cannot functionally replace TGase 1 action (14).…”
mentioning
confidence: 99%
“…During citrullination by PAD3, THH aggregates loosen their structure, making them more susceptible to crosslinking catalyzed by transglutaminase. THH complexed with both keratins leads to the formation of structures that are stable and insoluble in water (Tarcsa et al 1997).…”
Section: Epidermal Keratinizationmentioning
confidence: 99%
“…It is an essential structural protein responsible for the mechanical strength of the hair follicle inner root sheath (Tarcsa et al 1997). After synthesis THH form insoluble structures which are stabilized by ionic interactions between the alpha helices (Lee et al 1993).…”
Section: Epidermal Keratinizationmentioning
confidence: 99%